DETERMINAN INTENSI WHISTLEBLOWING DENGAN INSENTIF WHISTLEBLOWING SEBAGAI VARIABEL MODERASI - Sholihun Sholihun; Harti Budi Yanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study discusses the factors that influence whistleblowing intention. The research data were obtained through electronic or printed questionnaires to external auditors. Selected respondents are auditors who work at the Public Accounting Firm in Jakarta. Based on the answers from 142 respondents, it is empirically proven that organizational commitment, anonymous reporting channels and the seriousness of violations have a positive effect on whistleblowing intentions. The next finding is that the personal cost variable is proven to have a negative effect on whistleblowing intention. The moderating variable, namely the whisle blowing incentive, is proven to strengthen the negative effect of personal cost on whistleblowing intention. Another interesting result is that the whistleblowing incentive does not strengthen the positive influence of organizational commitment variables, anonymous reporting channels and the seriousness of violations on whistleblowing intentions.